The minority within the minority: Refugee community-based organisations in the UK and the impact of restrictionism on asylum-seekers - Zetter, R; Pearl, M (2000)
Since the mid-1990s, policies and legislation for refugees and asylum-seekers have become increasingly restrictionist in the UK. Disentitlement to housing and welfare benefits and fragmented service delivery have caused widespread social exclusion and destitution amongst asylum-seekers. The article examines some of the consequences of these policy shifts for refugee community-based organisations (RCOs). The article shows how, on the margins, RCOs have articulated the needs and expanded their activities for their client groups in an increasingly constrained policy arena. However, the vital resources that RCOs could provide are often as neglected and marginalised as the groups they serve. Financial and legal constraints to RCO action have resulted in pragmatic responses, a generally poor quality of service provision, very limited access to public resources, lack of co-ordination and networking, and limited professional capacity. These shortcomings are underpinned by institutional and structural determinants which the 1999 Immigration and Asylum Act reinforces. These flaws in the current framework of provision are explored. Some ways in which practice can be improved are outlined. Pessimistically the article concludes that, despite the rapid increase of demand for RCO services, the scope for major repositioning of RCOs away from the margins is unlikely.